Hungry Porphyrins: Protonation and Self‐Metalation of Tetraphenylporphyrin on TiO2(110) ‐ 1 × 1. Issue 19 (17th November 2016) - Köbl, Julia; Wang, Tao; Wang, Cici; Drost, Martin; Tu, Fan; Xu, Qian; Ju, Huanxin; Wechsler, Daniel; Franke, Matthias; Pan, Haibin; Marbach, Hubertus; Steinrück, Hans‐Peter; et al.
Abstract: We have studied the adsorption and self‐metalation of tetraphenylporphyrin (2HTPP) on TiO2 (110) ‐ 1 × 1 with X‐ray Photoelectron Spectroscopy (XPS) and Scanning Tunneling Microscopy (STM). Upon adsorption at room temperature the first monolayer of 2HTPP is protonated by protons from the surface, forming porphyrin diacid (4HTPP 2+ ). In STM, single molecules with low mobility and no long‐range order were observed. As the surface is heated to 400 K, any unprotonated 2HTPP molecules in the second layer metalate, forming titanyl tetraphenylporphyrin (TiOTPP), but the protonated molecules in the first layer remain. As the surface is heated further to 550 K even the protonated 4HTPP 2+ molecules metalate and only TiOTPP remain on the surface. Abstract : "Snacking" Tetraphenylporphyrin Molecules: At elevated temperatures tetraphenylporphyrin molecules deposited on titania reacts with the surface, picking up Ti=O 2+ units from the surface and becoming titanyl tetraphenylporphyrin.